PHOTOPROBER® Biotin: An Alternative Method for Labeling Archival DNA for Comparative Genomic Hybridization - Dirk Korinth; Konrad Donhuijsen; Ulrike Bockmühl; Iver Petersen (Cellular Oncology)
Comparative genomic hybridization (CGH) represents a powerful method for screening the entire genome of solid tumors for chromosomal imbalances. Particularly it enabled the molecular cytogenetic analysis of archival, formalin‐fixed, paraffin‐embedded (FFPE) tissue. A well‐known dilemma, however, is the poor DNA quality of this material with fragment sizes below 1000 bp. Nick translation, the conventionally used enzymatic DNA labeling method in CGH, leads to even shorter fragments often below a critical limit for successful analysis. In this study we report the alternative application of non‐enzymatic, PHOTOPROBE® biotin labeling for conjugation of the hapten to the DNA prior to in situ hybridization and fluorescence detection. We analyzed 51 FFPE tumor samples mainly from the upper respiratory tract by both labeling methods. In 19 cases, both approaches were successful. The comparison of hybridized metaphases showed a distinct higher fluorescence signal of the PHOTOPROBE® samples sometimes with a discrete cytoplasm background which however did not interfere with specificity and sensitivity of the detected chromosomal imbalances. For further 32 cases characterized by an average DNA fragment size below 1000 bp, PHOTOPROBE® biotin was the only successful labeling technique thus offering a new option for CGH analysis of highly degraded DNA from archival material.